Comparative analysis of the spatial distribution and severity of cerebral microbleeds and old lacunes. Issue 3 (13th February 2004) - Lee, S-H; Bae, H-J; Ko, S-B; Kim, H; Yoon, B-W; Roh, J-K
Abstract : Background: Cerebral microbleeds, which result from microangiopathic changes following chronic hypertension, may reflect bleeding-prone microangiopathy. However, the distribution of these lesions has not been compared with that of lacunes, which represent occlusive type microangiopathy. Objectives: To compare the cerebral distribution of microbleeds and lacunes and correlate their severity. Methods: The study population comprised 129 hypertensive patients who underwent brain magnetic resonance imaging (MRI), including gradient echo (GE) sequences. Cerebral microbleeds were counted using GE-MRI data, and lacunes were also counted by comparing T1 and T2 weighted MRI. To investigate the distributions, the number of patients with each type of lesion was compared, and the occurrence index (the total number of the specific lesions divided by the total number of patients) was examined statistically. Correlation analyses were done on the relations between the different grades of microbleeds, lacunes, and leukoaraiosis. Results: Cerebral microbleeds and lacunes were found at various foci in the brain, with a preference for the cortico-subcortical region and the deep grey matter. The occurrence index of microbleeds, but not of lacunes, was significantly higher in the cortico-subcortical region than in the deep grey matter. The severity of the microbleeds was positively correlated with the severity of lacunes, and both types of lesion were closely correlated with the degree of leukoaraiosis. Conclusions: These data suggest that microbleeds and lacunes tend to occur to a similar extent in long standing hypertension, but not necessarily in the same locations.